Influence of Targeted Tibial Rotation Exercises on Knee Biomechanics and Patient-Reported Outcomes in Patellofemoral Pain Syndrome - Shrimali, Divyank; Pal, Renuka; Khan, Jafar; Annamalai, KM.; Lohar, Deepak; Sharma, Deepak; Rai, Richa Hirendra (Journal of Neonatal Surgery, 2025)
Background: Quadriceps-dominant rehabilitation remains the mainstay for patellofemoral pain syndrome (PFPS), yet aberrant tibial rotation has been implicated in mal-tracking and residual pain. Objective: To determine whether adding explicit tibial-rotation control to a balanced hamstring–quadriceps strengthening programme yields superior pain relief and functional gains compared with conventional strengthening alone. Methods: This secondary analysis used data from a randomised, single-centre comparative study involving 30 adults with chronic PFPS (18–60 y). Participants were allocated to (A) hamstring-quadriceps strengthening with tibial-rotation exercises or (B) the same protocol without tibial rotation. Both groups trained 30 min·session⁻¹, five days·week⁻¹ for six weeks. Primary outcomes were pain (10-cm Visual Analogue Scale, VAS) and knee function (Kujala Anterior Knee Pain Scale). Within-group change was assessed with paired t-tests; between-group differences with independent t-tests (α = 0.05). Results: Twenty-nine participants (A = 15; B = 14) completed follow-up. Group A demonstrated larger VAS reduction (-4.13 ± 1.02 vs -2.00 ± 1.06 cm; p < 0.001) and greater Kujala improvement (+25.3 ± 5.1 vs +20.2 ± 4.8 points; p < 0.001). Post-intervention VAS (2.47 ± 0.83 cm) and Kujala scores (85.5 ± 3.1) in Group A were significantly better than Group B (4.47 ± 0.83 cm; 78.9 ± 3.6, respectively). No adverse events occurred. Conclusion: Integrating targeted tibial-rotation drills into conventional lower-limb strengthening produced clinically and statistically superior pain and functional outcomes in PFPS over six weeks. Addressing rotational biomechanics appears to augment traditional muscle-centric protocols and should be considered in routine rehabilitation